The social psychology of responses to trauma: social identity pathways associated with divergent traumatic responses. Issue 1 (1st January 2019) - Muldoon, Orla T.; Haslam, S. Alexander; Haslam, Catherine; Cruwys, Tegan; Kearns, Michelle; Jetten, Jolanda
ABSTRACT: Research in clinical psychology and social psychiatry has highlighted the importance of social factors for outcomes following trauma. In this review, we speak to this issue in two ways. First, we highlight the value of a social identity framework for understanding the experience and impact of psychological trauma. Second, we draw on the Social Identity Model of Identity Change (SIMIC) to understand reactions to trauma. Specifically, we show (a) that negative responses to trauma are more apparent where trauma serves to undermine valued social identities; (b) that people prove more resilient in the face of trauma when valued social identities can be maintained or new social identities developed; and (c) that where old or new positive identities are reinvigorated or extend the self, this can be a basis for post-traumatic growth. We conclude by discussing the implications of this model for practice, and emphasise the importance of social identity management in the aftermath of trauma.